THE USAGE OF EDMODO SOFTWARE IN THE LEARNING OF MATHEMATICS AND ITS EFFECT TOWARD STUDENT RESILIENCE - HamzahMalajun; Mad Noor Majapuni; Tan Choon Keong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In today’s education system, it requires creativity and effective strategy for the teaching and learning system to run smoothly. Not to mention the pandemic happening nowadays requires efforts among the educators to create a new education system that could fulfill the teaching and learning needs. However, the lack of usage and efficiency in implementing online teaching activities in integrating ICT facilities has become a constraint in having a successful online education system. Therefore, more research should be conducted by combining ICT with the implementation of the current education system. In that notion, this research is conducted by studying the use of the Edmodo software in Mathematics learning especially on the effect on student’s resilience. The objective of this research is to study the learning scenario and concept in using the Edmodo network platform and explore the development of resilience in the overall context through online mathematics learning using Edmodo. This is qualitative research conducted among 10 form 4 students in Kudat. Findings from this research are self-regulated strategies for using Edmodo systematically in mathematics lessons among students in various adaptation stages. Next, the result of this research also found the effects of using the platform in creating resilience among the students in terms of changes in their behavior by showing commitment and continuous effort. The implications of this research will provide the opportunity for researchers in the future who wish to pursue research in mathematics education from a different perspective especially the combination of ICT facilities. At the same time, this research can be a practical solution in today's challenges in online teaching and learning implementations.